Mechanical properties of concrete containing beeswax/dammar gum as phase change material for thermal energy storage - Umar H.; Rizal S.; Riza M.; Mahlia T.M.I. (AIMS Press, 2023)
Compressive strength; Concrete mixtures; Concrete products; Food products; Heat storage; Light weight concrete; Melting point; Mixtures; Thermal conductivity; Waxes; Beeswax; Concrete; Concrete compressive strength; Energy content; Heat energy; Material mixture; Material property test; Properties of concretes; Strength tests; Thermal energy storage; Phase change materials